A comparative study on CuFe2O4, ZnFe2O4 and NiFe2O4: Morphology, Impedance and Photocatalytic studies. (2017) - Shetty, Krushitha; Renuka, L.; Nagaswarupa, H.P.; Nagabhushana, H.; Anantharaju, K.S.; Rangappa, Dinesh; Prashantha, S.C.; Ashwini, K.
Abstract: The spinel CuFe2 O4, ZnFe2 O4 and NiFe2 O4 were synthesized by simple solution combustion synthesis (SCS) and characterized by powder X-ray diffraction (PXRD), Fourier Transform Infrared Spectroscopy (FTIR), UV-Visible Spectroscopy and Scanning Electron Microscopy (SEM). PXRD result showed spinel nature for the prepared ferrites. SEM results displayed spinel morphology with numerous flakes. Electrochemical Impedance Spectroscopy (EIS) was employed to study the charge carrier recombination rate. Photodecomposition ability is studied by carrying out the photocatalytic experiments for the synthesized nanoferrites under visible light. The synthesized nanoferrites showed distinguished behaviour with respect to optical, electrochemical and photocatalytic performance. These results demonstrate that the synthesized samples can be useful for water remediation.